Size-controllable growth of ZnO nanorods on Si substrate. (January 2017) - Yu, Zhentao; Li, Hui; Qiu, Yining; Yang, Xu; Zhang, Wu; Xu, Ning; Sun, Jian; Wu, Jiada
Abstract: Here we report a simple two-step chemical-solution-based method to grow highly oriented and size-controllable ZnO nanorods on ZnO-seeded Si substrate. The morphology of the grown ZnO nanorods was examined by field emission scanning electron microscopy. The structure was characterized by X-ray diffraction and Raman scattering spectrum. Photoluminescence spectra were measured at room temperature and low temperatures to evaluate the photoluminescence properties of the ZnO nanorods. The grown ZnO nanorods are structured with hexagonal wurtzite. The diameter and length of ZnO nanorods can be controlled by varying the crystal quality of the underlying ZnO seed layers. The crystal quality of the seed layers gets improved as the deposition time and annealing temperature for ZnO seed layers are increased. The effects of annealing on the ZnO nanorods were also studied. Graphical abstract: Highlights: Size-controllable growth of oriented ZnO nanorods on ZnO-seeded Si was demonstrated. ZnO nanorods were grown by hydrothermal method at a temperature as low as 65 °C. The diameter and length of ZnO nanorods depend on the crystal quality of seed layer. The size of nanorods can be controlled by changing the deposition time of seed layer. The size can also be controlled by varying the annealing temperature of seed layer.